Multicriteria approach for service units location: proposal of method SMARTER application - Lopes, Yuri Gama (2009)
Among the various types of decision present during the planning and business management process, location decision is a critical factor to organization development, as much in their own business activities, as in the company performance in the supply chain in which it is included, which involves its customers satisfaction, logistics costs and operational results. Particularly, the location of service units of involves a greater amount of subjective factors, hampering the use of traditional decision models to tackle the location problem. Such models, in their majority, have methodological problems in its analysis and calculus procedures, especially in the decision-maker preferences structuring and in the mullticriteria agreggation procedures. This paper seeks structure methodologically the multicriteria decision making to locate service units. For this, it is proposed the use of the method SMARTER (Simple Multi-Attribute Rating Technique using Exploiting Rankings), and a numerical application is described.